Influence of tobacco on median and ulnar nerve in the population of South Rajasthan - Sharma, Suman; Shrivastav, Chanchal; Suhalka, M. L.; Kaur, Manjinder (International Journal of Research in Medical Sciences, 2016)
Background: Chemicals present in tobacco have been implicated in causing subclinical changes in myelin sheaths of peripheral nerves. This may contribute to nerve dysfunction particularly in the form of decreases in nerve conduction velocity. So, present study aims to measure nerve conduction velocity in the median nerve and ulnar nerve among tobacco users. Methods: This was a cross-sectional case-control study involving 50 normal healthy subjects and 150 tobacco users. The nerve conduction study was performed using fully computerized electromyography (EMG) and nerve conduction velocity (NCV) machine. By this machine Sensory nerve conduction velocity (SNCV) and Motor nerve conduction velocity (MNCV) tests of both the nerves (median and ulnar) was performed on subjects. Data was analyzed by using appropriate statistical methods. Results: In our study statistically significant changes (P < 0.001) were found in the Sensory nerve conduction velocity of both the nerves whereas no such changes were found in Motor nerve conduction velocity of both the nerves in tobacco users as compared to nontobacco users. Conclusions: We conclude that use of tobacco results in reduction of conduction velocities in sensory fibers of the median nerve and ulnar nerve but not in motor fibers.